Intensification of endurance training with superimposed electrostimulation: acute hormonal & metabolic responses - Wahl, P.; Hein, M.; Achtzehn, S.; Mester, J. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
High intensity interval training (HIT) has been shown to be an effective and time saving strategy to improve endurance performance. Electromyostimulation (EMS) is a training method mainly performed in strength training and is used for its intensification. However, up to now, only one study (Wahl et al. 2012) investigated the applicability and effects of superimposed EMS during endurance exercise. Therefore, the aim of the present study was to quantify the effects of local EMS during cycling on the hormonal system, the acid-base balance, the muscular demand, and the perceived exertion.